The Influence of Participatory Leadership on The Development of Teacher Competence in The Era of The Industrial Revolution 4.0 (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This study aims to analyze the influence of participatory leadership on teacher competency at SMP Negeri 4 Probolinggo City in facing the challenges of the Industrial Revolution 4.0. Using a quantitative approach with a correlational method, this study involved 50 teachers selected through purposive random sampling. The instrument, a participatory leadership questionnaire and teacher competency, were analyzed through regression and Pearson correlation. The results show a positive and significant relationship between participatory leadership and teacher competency, with a correlation value (r) of 0.72 and a coefficient of determination (R²) of 0.518. This finding indicates that participatory leadership contributes 51.8% to teacher competency development. The implications of this study emphasize the importance of the principal's role in implementing a collaborative participatory leadership style to support teacher professional development and create a school climate that is adaptive to technological developments.